APPLICATION OF DYNAMIC PROGRAMMING IN DETERMINING THE SHORTEST ROUTE PT JNE USING BACKWARD RECURSIVE EQUATION - Maudya Nur Azura; Riri Syafitri Lubis (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
Technological progress speeds up human movement, the distribution of goods, and service provision. PT JNE, a prominent firm in Indonesia, concentrates on delivering goods swiftly and with comprehensive services.. On the other hand, problems include daily changes in delivery, delays, less than optimal routes, and expensive gasoline. The shortest ideal route for the transportation of products is found using dynamic programming and a backward recursive equation technique in this study. The Medan Belawan District as well as the JNE Medan Representative Office provided the data that was used. The findings show that a route of a → f → d → c → g → b → e → h → a is the ideal total distance for goods delivery using a dynamic programming graph is 12,2 km, with an average courier covering 16,5 km. Based on data analysis, this shows a 26% increase in efficiency over the current routes. The layout of the routes makes it easier for couriers to choose the fastest route.